Linguistic inter-understanding gives evidence in favor of the mental models theory: Induction and comprehension - López-Astorga, Miguel (Aufklärung: journal of philosophy, 2017)
Linguistic inter-understanding is a communicative phenomenon that is well known and that has been studied in detail. It basically consists of the fact that an individual speaking a language is able to understand another person speaking a different language, and this without deeply knowing this last language or being able to express himself/herself in it. The phenomenon, which is especially frequent in the case of very similar languages, occurs because of certain inferential processes that can happen in the human mind when people try to interpret information in a distinct language. In this way, the main aim of this paper is to show how such processes are very akin to some of those that the mental models theory attributes to the human reasoning ability, and that hence linguistic inter-understanding can be considered as evidence that this last theory is, at least partially, correct.